2003
DOI: 10.1046/j.1365-313x.2003.01798.x
|View full text |Cite
|
Sign up to set email alerts
|

An Arabidopsis porB porC double mutant lacking light‐dependent NADPH:protochlorophyllide oxidoreductases B and C is highly chlorophyll‐deficient and developmentally arrested

Abstract: The first and second authors contributed equally to this work. SummaryA key reaction in the biosynthesis of chlorophylls (Chls) a and b from cyanobacteria through higher plants is the strictly light-dependent reduction of protochlorophyllide (Pchlide) a to chlorophyllide (Chlide) a. Angiosperms, unlike other photosynthetic organisms, rely exclusively upon this mechanism to reduce Pchlide and hence require light to green. In Arabidopsis, light-dependent Pchlide reduction is mediated by three structurally relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
123
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(137 citation statements)
references
References 52 publications
12
123
0
2
Order By: Relevance
“…Our results showed that chlorophyll contents were low in pop2-3 mutant than wild-type plant after 30 days in normal growth condition. Probably low chlorophyll content in mutant showed precocious leaf senescence [ Figure 1a], which was similar to the reported data in egy1 mutants, [27] porB1porC-1 double mutant of older seedlings, [30] and mex1 leaves of A. thaliana. [31] The chlorophyll content of GABA-T complement plant was approximately similar to wild-type plant up to 30 days [ Figure 1a].…”
Section: Discussionsupporting
confidence: 89%
“…Our results showed that chlorophyll contents were low in pop2-3 mutant than wild-type plant after 30 days in normal growth condition. Probably low chlorophyll content in mutant showed precocious leaf senescence [ Figure 1a], which was similar to the reported data in egy1 mutants, [27] porB1porC-1 double mutant of older seedlings, [30] and mex1 leaves of A. thaliana. [31] The chlorophyll content of GABA-T complement plant was approximately similar to wild-type plant up to 30 days [ Figure 1a].…”
Section: Discussionsupporting
confidence: 89%
“…2). Protein analysis of the EX1-GFP immunoprecipitate by mass spectrometry and Western blots revealed that EX1 forms part of a larger physical unit in grana margins that, in addition to the RC of PSII and several PSII light-harvesting Chl a/b proteins, comprises also chloroplast-specific subunits of the FtsH protease, the NADPHprotochlorophyllide oxidoreductases (POR) B and C catalyzing the light-dependent reduction of Pchlide to Chlide (21,22), the Tic110 protein translocation channel, the Ca 2+ -sensing protein and the GTP-binding Tu, and RAB GTPase homolog E1B elongation factors (Table S1 and Fig. S2).…”
Section: Resultsmentioning
confidence: 99%
“…Transgenic seedlings grown under far red light when transferred to white light are more resistant to photobleaching because of high POR proteins. 75 The isolation and studies on Arabidopsis flu mutant by Klaus Apel's group confirm the role of Pchlide in 76 In the flu mutant there is no regulatory point at the GluTR level and there is a massive accumulation of Pchlide. Lee et al 77 have revealed that the TIGRINA d gene of barley is an ortholog of the FLU gene of Arabidopsis thaliana.…”
Section: Singlet Oxygen-induced Oxidative Damage In Mutantsmentioning
confidence: 91%